Respostas
respondido por:
4
2x - 14 = 4x + 10
2x - 4x = 10 + 14
-2x = 24
x = 24/-2
x = -12
2x - 4x = 10 + 14
-2x = 24
x = 24/-2
x = -12
respondido por:
2
2x - 14 = 4x + 10
4x - 2x = -14 - 10
2x = -24
x = -24/2
x = -12
Prova:
2.(-12) - 14 = 4.(-12) + 10
-24 - 14 = -48 + 10
-38 = -38 (verdade)
Espero ter ajudado.
4x - 2x = -14 - 10
2x = -24
x = -24/2
x = -12
Prova:
2.(-12) - 14 = 4.(-12) + 10
-24 - 14 = -48 + 10
-38 = -38 (verdade)
Espero ter ajudado.
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás